(untitled) (Principles and Practice of Clinical Research, 2025)
Background Fibromyalgia is a chronic disorder characterized by widespread pain and fatigue. Recent evidence suggests that inflammation may play a role in fibromyalgia's pathophysiology. The COVID-19 pandemic has introduced long-COVID, a condition with overlapping symptoms to fibromyalgia, prompting further investigation into shared inflammatory pathways. Objective To evaluate the association between inflammatory markers and fibromyalgia in humans, assess the relevance of animal models in studying these markers, and explore the similarities and differences in inflammatory markers between fibromyalgia and long-COVID patients. Methods A systematic review was conducted using PubMed, Medline, Embase, and Scopus databases. Studies involving human participants with fibromyalgia, animal models of fibromyalgia, and long-COVID patients with fibromyalgia-like symptoms were included. Data on inflammatory markers were extracted, and the quality of studies was assessed. A meta-analysis was performed where possible. Results Elevated levels of IL-6, TNF-α, and CRP were consistently reported in fibromyalgia patients compared to controls. Animal models corroborated these findings, demonstrating similar inflammatory profiles. In long-COVID patients, IL-6 and TNF-α levels were also elevated, suggesting shared inflammatory pathways with fibromyalgia. Conclusion Inflammatory markers such as IL-6 and TNF-α are elevated in both fibromyalgia and long-COVID patients, indicating potential commonalities in their pathophysiological mechanisms. This highlights the need for targeted anti-inflammatory therapies and further research into the inflammatory basis of these conditions. Keywords Fibromyalgia, Long-COVID, Inflammatory Markers, Cytokines, Systematic Review, Meta-Analysis